Urban Churches Show an Increase in Attendance, Donations, and Finances During the COVID-19 Pandemic in the USA: Evidence from the United Methodist Church - Niazi, Anum G. (Journal of religion and health, 2024)
The COVID-19 pandemic has had a significant impact on religion and its practice. This paper aims to examine how the pandemic affects religious activities, donations, and finances over time and across regions within the United Methodist Church (UMC) in the USA. To address this question, we analyze survey data collected during the pandemic from 2963 churches in the USA by United Methodist Communications. Our analysis utilizes several quantitative techniques, including Z-tests, one-way analysis of variance (ANOVA), and multinomial logistic regressions. The results indicate a decrease in church attendance over time, with a more pronounced effect observed in non-urban areas (suburban, small town, and rural). Similarly, while church donations and finances mitigate over time across churches, churches in urban areas experience a quicker rebound compared to those in non-urban areas. Lastly, we find that church attendance and donations positively affect finances. These findings hold important implications for churches in various regions, offering insights to develop strategies for navigating the challenges posed by the COVID-19 pandemic.